Silly Sara : a phonics reader - Hays, Anna Jane (New York : Random House, 2002)
Alliterative rhyming tale of a girl who can be very silly but with her best frien, Sam, she discovers she can be something more.
Keywords: Clumsiness -- Fiction; Best friend -- Fiction; Stories in rhyme